Hybrid stage 1 palliation for HLHS: the experience of a tertiary center in a developing country - Bitar, Fouad; El-Rassi, Issam M.; Zareef, Rana; Jassar, Yehya; Abboud, Jennifer; Bulbul, Ziad; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2024)
Background: Hypoplastic left heart syndrome (HLHS) accounts for 2.6% of congenital heart disease and is an invariably fatal cardiac anomaly if left untreated. Approximately 33,750 babies are born annually with HLHS in developing countries. Unfortunately, the majority will not survive due to the scarcity of resources and the limited availability of surgical management. Aim: To describe and analyze our experience with the hybrid approach in the management of HLHS in a developing country. Methods: We performed a retrospective single-center study involving all neonates born with HLHS over five years at the Children’s Heart Center at the American University of Beirut. The medical records of patients who underwent the hybrid stage 1 palliation were reviewed, and data related to baseline characteristics, procedure details and outcomes were collected to describe the experience at a tertiary care center in a developing country. Results: A total of 18 patients were diagnosed with HLHS over a five-year period at our institution, with male to female ratio of 1:1. Of those, eight patients underwent the hybrid stage I procedure. The mean weight at the time of the procedure was 3.3 ± 0.3 kg with an average age of 6.4 ± 4 days. The mean hospital length of stay was 27.25 days, with an interquartile range of 33 days. The cohort's follow-up duration averaged 5.9 ± 3.5 years. The surgical mortality was zero. Only one mortality was recorded during the interstage period between stage I and II and was attributed to sepsis. Notably, all surviving patients maintained preserved and satisfactory cardiac function with good clinical status. Conclusion: Our limited experience underscores the potential of developing countries with proper foundations to adopt the hybrid procedure for HLHS, yielding outcomes on par with those observed in developed countries. This demonstrates the viability of establishing a more balanced global landscape for children with congenital heart disease.